Удосконалення конструкції гарнісажної фурми та технології відновлення профілю робочого простору конвертера - Сігарьов, Є.М.; Недбайло, М.М.; Байдуж, Ю.В. (Physico-technological Institute of Metals and Alloys, 2023)
The article deals with the problems of «splash-slag» technology for the lining of the oxygen converter by blowing the converter’s slag, previously modified by magnesia additives, with the use of special lances.